Weaning strategies for the withdrawal of non-invasive respiratory support applying continuous positive airway pressure in preterm infants: a systematic review and meta-analysis - Brenda van Delft; Filip Van Ginderdeuren; Julie Lefevere; Christel van Delft; Filip Cools (BMJ Paediatrics Open)
Background The optimal method to wean preterm infants from non-invasive respiratory support (NIVRS) with nasal continuous positive airway pressure (CPAP) or high-flow nasal cannula is still unclear, and methods used vary considerably between neonatal units.Objective Perform a systematic review and meta-analysis to determine the most effective strategy for weaning preterm infants born before 37 weeks’ gestation from NIVRS.Method EMBASE, MEDLINE, CINAHL, Google and Cochrane Central Register of Controlled Trials were searched for randomised controlled trials comparing different weaning strategies of NIVRS in infants born before 37 weeks’ gestation.Results Fifteen trials (1.547 infants) were included. With gradual pressure wean, the relative risk of successful weaning at the first attempt was 1.30 (95% CI 0.93 to 1.83), as compared with sudden discontinuation. Infants were weaned at a later postmenstrual age (PMA) (median difference (MD) 0.93 weeks (95% CI 0.19 to 1.67)). A stepdown strategy to nasal cannula resulted in an almost 3-week reduction in the PMA at successful weaning (MD −2.70 (95% CI −3.87 to −1.52)) but was associated with a significantly longer duration of oxygen supplementation (MD 7.80 days (95% CI 5.31 to 10.28)). A strategy using interval training had no clinical benefits. None of the strategies had any effect on the risk of chronic lung disease or the duration of hospital stay.Conclusion A strategy of gradual weaning of airway pressure might increase the chances of successful weaning. Stepdown strategy from CPAP to nasal cannula is a useful alternative resulting in an earlier weaning, but the focus should remain on continued weaning in order to avoid prolonged oxygen supplementation. Interval training should probably not be used.